Neurocognitive and Neuromuscular Rehabilitation Techniques after ACL injury - Part 2: Maximizing Performance in the Advanced Return to Sport Phase - Zachary M. Thomas; Lewis Lupowitz; Morgan Ivey; Kevin E. Wilk (International Journal of Sports Physical Therapy)
# Background